2010
DOI: 10.1007/s12600-010-0100-1
|View full text |Cite
|
Sign up to set email alerts
|

The phytotoxicity potential of olive processing waste on selected weeds and crop plants

Abstract: The effect of sun-dried OPW (olive processing waste) on weeds and crop plants, was investigated at the Adnan Menderes University Research and Application Farm between 2006 and 2007. Sun-dried OPW was placed in pots in doses of 9, 18, 27, 36, 45 and 54 grams per pot, which is equivalent to doses of 1, 2, 3, 4, 5 and 6 kg m −2 ; pots with no OPW served as controls. In these experiments, ten seeds each of wild oat (Avena ), sterile oat (fatua), sterile oat (Avena sterilis), blackgrass (Alopecurus myosuroides), pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In this sense, some research studies have demonstrated the selectivity of potential bioherbicides, using different weed species and testing them with olive water and compound extracts . Between weed plants and crops treated with olive water, plant extract, and fungi, ,, different levels indicated that crops treated with a plant-derived bioherbicide caused similar effects as those treated with glyphosate and glufosinate . Therefore, a selective and differential phytotoxicity test for bioherbicides can reveal sustainable weed control measures for agricultural use …”
Section: Advantages and Limitations Of Using Bioherbicidesmentioning
confidence: 99%
“…In this sense, some research studies have demonstrated the selectivity of potential bioherbicides, using different weed species and testing them with olive water and compound extracts . Between weed plants and crops treated with olive water, plant extract, and fungi, ,, different levels indicated that crops treated with a plant-derived bioherbicide caused similar effects as those treated with glyphosate and glufosinate . Therefore, a selective and differential phytotoxicity test for bioherbicides can reveal sustainable weed control measures for agricultural use …”
Section: Advantages and Limitations Of Using Bioherbicidesmentioning
confidence: 99%